2016
DOI: 10.1016/j.immuni.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania Uses Mincle to Target an Inhibitory ITAM Signaling Pathway in Dendritic Cells that Dampens Adaptive Immunity to Infection

Abstract: Summary C-type lectin receptors sense a diversity of endogenous and exogenous ligands that may trigger differential responses. Here, we have found that human and mouse Mincle bind to a ligand released by Leishmania, a eukaryote parasite that evades an effective immune response. Mincle-deficient mice had milder dermal pathology and a tenth of the parasite burden compared to wild-type mice after Leishmania major intradermal ear infection. Mincle deficiency enhanced adaptive immunity against the parasite, correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 45 publications
(96 reference statements)
4
77
1
Order By: Relevance
“…MR knockdown in hMDMs significantly reduced SHP-1 recruitment to phagosomal membranes demonstrating the dependence on MR signaling. Our data do not support a direct interaction between SHP-1 and FcRγ-chain as recently reported by Iborra et al (Iborra et al, 2016) which studied Mincle-mediated inhibitory signaling events in murine GMCSF-treated bone marrow-derived cells suggesting receptor and/or mammalian cell differences.…”
Section: Discussioncontrasting
confidence: 88%
“…MR knockdown in hMDMs significantly reduced SHP-1 recruitment to phagosomal membranes demonstrating the dependence on MR signaling. Our data do not support a direct interaction between SHP-1 and FcRγ-chain as recently reported by Iborra et al (Iborra et al, 2016) which studied Mincle-mediated inhibitory signaling events in murine GMCSF-treated bone marrow-derived cells suggesting receptor and/or mammalian cell differences.…”
Section: Discussioncontrasting
confidence: 88%
“…We therefore hypothesise that TDM-Mincle interaction activates SHP-1 to subsequently inhibit PI3K and phagosome maturation. Our study corroborates and extends the observation by Iborra and colleagues, which recently revealed the link between Mincle and SHP-1 during Leishmania infection [27]. These authors demonstrated that recognition of the parasites by Mincle triggers an inhibitory FcγR-SHP-1 axis in dendritic cells subsequently leading to down-regulation of Th 1 responses required for protective immunity to Leishmania parasites.…”
Section: Resultssupporting
confidence: 93%
“…Which are the ligands in A. pegreffii that are involved in such immunomodulatory effects remains an open question. Recently, the C‐type lectin receptors, recognizing carbohydrate ligands, seem to play a key role in triggering immunosuppressive functions of DCs by helminths . Interestingly, Ani s 7, among the major allergens in A. pegreffii , is indeed a glycoprotein …”
Section: Discussionmentioning
confidence: 99%